Frame by frame playback on the Internet video - Miyaji, C. (Advances in Intelligent Systems and Computing, 2015)
Although frame-by-frame is one of the important operation to see sports movement precisely, it is not implemented in the streaming videos on the Internet. This article introduces Smart-method, a new method of frame-byframe on the streaming videos. It is based on the combination of two methods, streaming and download; streaming is used for playback, the image download is used for frame-by-frame operation, and these operations are switched smoothly, users will not notice these switches. Smart-method is not only enables to see sports movement precisely it opens various applications possible on the Internet; attaching meta-data of the sports videos, flexible thumbnail, and editing (cut and join the videos) on the Internet